OTOMATISASI PENYIRAMAN TANAMAN JAMBU MADU BERDASARKAN WAKTU DAN KELEMBABAN TANAH BERBASIS ARDUINO - Wilda Rina Hasibuan; Joko Susilo; Andrio Prijaya (Jurnal Informatika Kaputama (JIK), 2021)
Soil moisture is one of the most influencing factors on the growth and development of a plant. Watering plants manually is considered quite long and time consuming, so by using technological innovations and information, a system is made that can monitor soil moisture and can automatically water plants. By using a soil moisture sensor that was built using the Arduino Uno microcontroller and added with a timer and date sensor, you can do watering 2 times a day. Based on the test results show the value of soil moisture with wet soil conditions by getting an output value below 750 then the machine automatically turns off and does not water the plants and the value of soil moisture with dry soil conditions by getting an output value above 750 then the machine will automatically turn on and water plant. This research is expected to be a solution to existing problems by providing convenience in the process of watering plants regularly.